2021
DOI: 10.3390/su13041691
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Aided Design and Prediction of Environmentally Friendly Rubberised Concrete

Abstract: Not only can waste rubber enhance the properties of concrete (e.g., its dynamic damping and abrasion resistance capacity), its rational utilisation can also dramatically reduce environmental pollution and carbon footprint globally. This study is the world’s first to develop a novel machine learning-aided design and prediction of environmentally friendly concrete using waste rubber, which can drive sustainable development of infrastructure systems towards net-zero emission, which saves time and cost. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The MSE is a metric that tells the distance, or how far apart, are the predicted values from the observed, in this case experimentally determined, values in a dataset. According to earlier studies the number of neurons in the hidden layer is an essential parameter influencing the accuracy of the ANN [15]. A too large number of neurons in the hidden layer may lead to overfitting while a too low number may result in underfitting issues [16].…”
Section: Methodsmentioning
confidence: 99%
“…The MSE is a metric that tells the distance, or how far apart, are the predicted values from the observed, in this case experimentally determined, values in a dataset. According to earlier studies the number of neurons in the hidden layer is an essential parameter influencing the accuracy of the ANN [15]. A too large number of neurons in the hidden layer may lead to overfitting while a too low number may result in underfitting issues [16].…”
Section: Methodsmentioning
confidence: 99%
“…Although concrete can incorporate a large variety of components, some of them by-products or other industries, e.g., with treated palm oil fuel ash, the use of the ANN in predicting the compressive strength has proven to yield accurate results [16]. Other studies have shown the suitability of using the ANN when it comes to rubberized concrete [17] and concrete using fly-ash as a partial substitute for Portland cement [18]. It should be pointed out that even slight changes in concrete composition may result in different values for the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning technique has been widely used in civil and railway applications especially for predicting the properties of materials of track components based on the proportion of the ingredients e.g. recycled concrete [23], rubberised concrete [24] etc. More examples on railway track applications includes track response quantification [25], train weight prediction [26], fault detection [27][28][29][30], railway safety and accident identification [31,32].…”
Section: Introductionmentioning
confidence: 99%